Aproximaciones a un modelo de desarrollo a partir de la satisfacción con la vida - Londoño , Sandra Liliana (2022)
Satisfaction with life can be a proxy indicator of the complex phenomenon of human and social development, with satisfaction with life being understood as subjectively interpreted outcome, which is socially repeated due to its alignment with collectively valued goals. Satisfaction with life can be affected by changes in some variables analyzed theoretically and statistically, such as functional capacities, goods, trust, choice of values, perception of the governability of the country, and the functioning of democracy, which are studied empirically here. For the estimation of the models which result from this interpretation of human development, databases of the World Values Survey and the European Values Survey in the year 2000 for 31 countries were utilized. Empirical results suggest that satisfaction with life as an indicator of human development is affected mainly by the interpretation of the personal conditions (functional capacity) and the effective material wealth of the person.